1996
DOI: 10.1046/j.1523-1739.1996.10020515.x
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat and Landscape Characteristics Associated with the Threatened Allegheny Woodrat

Abstract: Populations of Allegheny woodrat (Neotoma magister) in the northeastern U.S. have declined recently for unexplained reasons. The species is believed to be separate from the more widely distributed eastern woodrat (Neotoma floridana; Ord 1818) and is listed as threatened in Pennsylvania. Several hypotheses have been proposed for the decline in N. magister, but little information on the ecology of the species is available to direct conservation efforts. Using a multi‐scale approach, we compared recent microhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 24 publications
1
48
2
Order By: Relevance
“…Occupancy also showed a trend toward higher occupancy along abandoned roads (p=0.12). Contrary to some of the previous research (Olsen 1973;Balcom & Yahner 1996;Gerber et al 2003), no forest metrics were found to be relevant to either the presence or occupancy of a woodrat nest.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Occupancy also showed a trend toward higher occupancy along abandoned roads (p=0.12). Contrary to some of the previous research (Olsen 1973;Balcom & Yahner 1996;Gerber et al 2003), no forest metrics were found to be relevant to either the presence or occupancy of a woodrat nest.…”
Section: Discussioncontrasting
confidence: 99%
“…Pilot surveys indicated that the average sighting distance by an observer searching for a nest was 14 m. On all surveys, observers walked along each transect and investigated all potential nest sites visible on either side. Though woodrats are known to build nests using a variety of materials (Goodyear 1985;McCleery 2003;McCleery et al 2006b;Winchester 2007;Winchester et al 2009), they will often use sticks to improve the nest site (Goodyear 1985;Balcom & Yahner 1996). I defined a nest as a feature exhibiting characteristic "stick-stacking", which is especially noticeable when underneath a ledge or other cover, and is easily distinguished from natural litterfall ( Figure 3).…”
Section: Nest Surveysmentioning
confidence: 99%
See 3 more Smart Citations